Funeral Traditions in The Mat Lou Ethnic Culture in Lilinta Village, Raja Ampat Island - Muhamad Yusuf; Enos Rumansara; Marlina Flassy; Erfin Wijayanti (Universitas Andalas, 2021)
This study aims to determine the implementation of the funeral ceremony in the Mat Lou ethnic community in Lilinta Village, West Misool District, Raja Ampat Islands. This research was qualitative using the social phenomenology paradigm with a flow chart model analysis. Results of this research: The culture of Raja Ampat community, especially in Lilinta village, which is Islam as a majority, has been through a culture diffusion and transformed with the existing local culture to produce a new culture. The cultures which are still conducted in the performance of various death are Tahlilan that has differences on its implementation, lifting the corpse using Koi (beds) where the other region in Indonesia those activities are conducted using coffins, the differences in making tombstone and also bones bath (Sof Kabom) which has various myth symbols in it. Immigrants have a role in spreading culture to bring up the assimilation of new cultural traits and elements of the Lilinta community in the form of other rituals that complement the death ritual